2021
DOI: 10.1039/d0ra09765a
|View full text |Cite
|
Sign up to set email alerts
|

External electric field effects on the σ-hole and lone-pair hole interactions of group V elements: a comparative investigation

Abstract: σ-hole and lone-pair (lp) hole interactions of trivalent pnicogen-bearing compounds were comparatively investigated under field-free and external electric field (EEF) conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 83 publications
0
27
0
Order By: Relevance
“…These results are in line with those of earlier studies related to the electric field effect on the σ-hole interactions. 70,71 Interaction Energy. Toward an in-depth investigation of the tetrel-bonding interactions, the interactions of F−T−F 3 molecules with FH were characterized, for the first time, in the absence and presence of an EEF.…”
Section: ■ Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…These results are in line with those of earlier studies related to the electric field effect on the σ-hole interactions. 70,71 Interaction Energy. Toward an in-depth investigation of the tetrel-bonding interactions, the interactions of F−T−F 3 molecules with FH were characterized, for the first time, in the absence and presence of an EEF.…”
Section: ■ Introductionmentioning
confidence: 77%
“…69 The directionality of the employed EEF was announced as the most influential parameter controlling the impact of the EEF on noncovalent interactions. 71 Along with the EEF directionality, the magnitude of the implemented EEF value substantially expressed its strength and significantly affected its role in regulating noncovalent interactions. 71 A recent theoretical study also sparked an upsurge of interest in the effect of the EEF's magnitude on the cation•••π interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Point-of-charge (PoC) approach was documented as an informative tool for elucidating the electrostatic inclination of the group III-VIII element-containing molecules to participate in noncovalent interactions [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. With the help of the PoC approach, negatively and positively charged points were utilized to parody the nucleophilic and electrophilic effects on the inspected molecular systems, respectively.…”
Section: Resultsmentioning
confidence: 99%
“… 67 , 68 Subsequently, a flurry of studies has been devoted to illustrating the EEF effect on variant noncovalent interactions. 69 72 Upon careful literature review, the EEF has demonstrated exceptional influence on the strength of the noncovalently bonded complexes. Nevertheless, there is a paucity in the literature relevant to its effect on versatile σ-hole and lp-hole interactions, in particular, within pnicogen-bearing complexes.…”
Section: Introductionmentioning
confidence: 99%